2021
DOI: 10.1109/access.2021.3115151
|View full text |Cite
|
Sign up to set email alerts
|

Combined Firm and Renewable Distributed Generation and Reactive Power Planning

Abstract: The benefits of integrating Distributed Generation (DG) into the distribution networks depend on the characteristics of different types of DG units, loads and Reactive Power Sources (RPS). These benefits can be optimized if the firm DG units such as biomass energy and renewable DG units such as photovoltaic (PV) and wind system are optimally sized, located and coordinated with reactive power sources. In this paper, by assuming that the Distribution System Operator (DSO) has got the ownership and operation of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The authors in Ref [15] created a smart method for energy organization of a PV, battery and wind based DC microgrid; however, the authors do not consider fuel cells or electrolyzers, and the system is not an AC microgrid. In Ref [16], authors offered a system for reactive power flow planning in a hybrid system based on renewable energy sources; nevertheless, the system is deficient in a fuel cell and an electrolyzer. The TSK-fuzzy controller could not be taken into consideration by the authors in [9]- [16] for quick response, and many of the articles did not use multilevel inverters to improve the voltage profile.…”
Section: System Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors in Ref [15] created a smart method for energy organization of a PV, battery and wind based DC microgrid; however, the authors do not consider fuel cells or electrolyzers, and the system is not an AC microgrid. In Ref [16], authors offered a system for reactive power flow planning in a hybrid system based on renewable energy sources; nevertheless, the system is deficient in a fuel cell and an electrolyzer. The TSK-fuzzy controller could not be taken into consideration by the authors in [9]- [16] for quick response, and many of the articles did not use multilevel inverters to improve the voltage profile.…”
Section: System Descriptionmentioning
confidence: 99%
“…In Ref [16], authors offered a system for reactive power flow planning in a hybrid system based on renewable energy sources; nevertheless, the system is deficient in a fuel cell and an electrolyzer. The TSK-fuzzy controller could not be taken into consideration by the authors in [9]- [16] for quick response, and many of the articles did not use multilevel inverters to improve the voltage profile.…”
Section: System Descriptionmentioning
confidence: 99%
“…New ideas and realities of electric energy generation, transmission, and distribution such as distributed generation (DG) and reactive power control, generate new requirements for active filtering strategies. SAFs are relied on to generate a given amount of reactive power to stabilize the voltage in transmission lines and increase the overall stability of distributed generation grids [23][24][25]. The main idea of distributed active filtering is to compensate for all microgrid current inactive components, mainly with embedded semiconductor converters of DG supplies.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that the presence of a DG system in the network has several advantages for distribution systems [13], such as an improvement in voltage stability [14], power quality [15,16], power loss reduction [17][18][19], and reactive power compensation [20]. In terms of system reliability, research has shown that optimal DG placement can improve the System Average Interruption Frequency Index and the System Average Interruption Duration Index in a distribution system [21].…”
Section: Introductionmentioning
confidence: 99%